Decision Support System for Recipients of Corporate Social Responsibility (CSR) Fund Assistance Using the Simple Additive Weighting Method (Case Study: PT Dexa Medica) - Raja Tegar Wahyudi (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
The effective and accurate management of community assistance fund data through a computerized system can ensure fast and transparent data processing. This study aims to design and develop a decision support system (DSS) capable of identifying eligible recipients of Corporate Social Responsibility (CSR) fund assistance, including financial aid for underprivileged individuals, scholarships, competition support, mosque construction, and COVID-19 relief. The proposed system enhances data collection and management efficiency. Currently, PT Dexa Medica implements CSR programs through conventional manual procedures, which require considerable processing time and often lead to inefficiency and errors. This study applies the Simple Additive Weighting (SAW) method, which utilizes 14 evaluation criteria, each assigned a specific weight corresponding to company priorities. The DSS developed in this research assists decision-makers in accurately determining eligible CSR fund recipients. The system is web-based, developed using the PHP programming language and a MySQL database.